2016
DOI: 10.1016/j.pec.2015.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Patient-health care professional gender or race/ethnicity concordance and its association with weight-related advice in the United States

Abstract: Objective Examine association between adult patients' and health care providers' (HCPs) gender or race/ethnicity concordance and patients' reported receiving weight-related advice from HCP's in USA. Methods Using Medical Expenditure Panel Survey (MEPS) 2004-2007 data, studied prevalence of weight-related advice (on exercise and diet) given to patients and its association with patients/HCPs concordance in gender (n=9,686) and race/ethnicity (n=8,825). Results Overall, 46% of patients received HCP advice on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…(n = 32) were conducted (in whole or part) in North American populations (Supplementary Table S1). 16,22,[24][25][26][27]31,33,35,38,39,[42][43][44][45][46]48,50,52,53,56,57,62,63,66,68,[71][72][73][74]77,78…”
Section: How This Fits Inmentioning
confidence: 99%
See 1 more Smart Citation
“…(n = 32) were conducted (in whole or part) in North American populations (Supplementary Table S1). 16,22,[24][25][26][27]31,33,35,38,39,[42][43][44][45][46]48,50,52,53,56,57,62,63,66,68,[71][72][73][74]77,78…”
Section: How This Fits Inmentioning
confidence: 99%
“…22 Patient-reported receipt of PA BI Twenty-five studies (reported in 26 articles) provided data on patient receipt of PA BI (Figure 2; Supplementary Table S4). 16,24,27,[31][32][33]38,40,41,43,44,47,48,[51][52][53][54][55]60,61,63,64,67,68,74,76 The proportion of patients reporting that they had received PA advice ranged from 7.7% (of females, 9.4% of males) to 76% (median 35%), 40,63 with 13 studies reporting that <40% of patients recalled receiving PA advi ce. 16,31,38,40,41,47,48,51,53,54,60,64,67 Reviewing audiotaped discussions highlighted that 21% of patients could not accurately recall PA discussions that occurred.…”
Section: Level Of Pa Screening By Health Professionalsmentioning
confidence: 99%
“…Patients’ ethnic background also seem to impact HCPs expression of compassionate care, with HCPs potentially expressing less affective compassion towards Korean patients, for example, due to a belief that patients from this ethnic group are less receptive to expressive feelings [ 49 ]. On the other hand, many Korean study patients preferred to be seen by a HCP from a different ethnic background because of fear of judgment from their fellow Korean HCP [ 54 ], thereby suggesting that patient-healthcare provider ethnicity concordance is not necessarily associated with enhanced compassionate care affirming the results of other studies [ 71 ]. Collectively, these results suggests that ethnic and cultural differences not only affect patients’ experiences of receiving compassion, but could also result in variance in HCPs’ provision of compassion—modifying their compassion based on the beliefs and assumptions they hold related to the ethnic background of the patient in their care.…”
Section: Discussionmentioning
confidence: 74%
“…This study focussed on patients’ perceptions of communication to inform future patient-centred care, however, future studies may wish to collect data from PCPs to address this limitation. Other factors not measured in this study may explain aspects of weight-related interactions in primary care, such as physician perception of the interaction, PCP weight stigma, low PCP weight control knowledge, brief appointments, or PCP demographics (Yang et al ., 2016 ; Tsai et al ., 2018a ). Additionally, this study focussed on patients enrolled in a research trial which may limit generalizability.…”
Section: Discussionmentioning
confidence: 99%